2010
DOI: 10.1093/mutage/geq050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age, gender, diet and lifestyle on DNA damage measured using micronucleus frequency in human peripheral blood lymphocytes

Abstract: Micronucleus (MN) frequency in cytokinesis-blocked peripheral blood lymphocytes (PBL) has become one of the best-established biomarkers for studying DNA damage occurring in vivo in humans. The application of this method in population biomonitoring studies requires a deep understanding of how lifestyle and common host variables may influence MN frequency in PBL. In this mini-review, an update is provided on results from studies reporting on the impact of age, gender, diet and lifestyle factors (e.g. exercise, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
168
6
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(203 citation statements)
references
References 82 publications
19
168
6
10
Order By: Relevance
“…Several studies found that increase of MN frequencies with an increasing age was followed by a decrease in proliferating efficiencies of cells [20][21][22]. The increase of MN frequencies with age can be due to several factors likes the cumulative effect of acquired mutations in genes involved in DNA repair, the numerical and structural aberrations in chromosomes caused by exposure to endogenous genotoxins, inadequate nutrition, exposure to environmental or occupational genotoxins, as well as a wide range of unhealthy lifestyle factors [23]. In this study we also found a higher of BI in female compared to male in all samples (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that increase of MN frequencies with an increasing age was followed by a decrease in proliferating efficiencies of cells [20][21][22]. The increase of MN frequencies with age can be due to several factors likes the cumulative effect of acquired mutations in genes involved in DNA repair, the numerical and structural aberrations in chromosomes caused by exposure to endogenous genotoxins, inadequate nutrition, exposure to environmental or occupational genotoxins, as well as a wide range of unhealthy lifestyle factors [23]. In this study we also found a higher of BI in female compared to male in all samples (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…MN is expressed in cells when either acentric chromosome fragments or whole chromosomes fail to be segregated to the daughter nuclei during mitosis 9) . It also seems that the CBMN assay can be used to measure not only whole chromosome loss or chromosome breaks but also excision-repair events 8,22) .…”
Section: Discussionmentioning
confidence: 99%
“…These all contributed to the overarching uncertainty surrounding the dose-response model and the final estimates. Third, unlike hepatic angiosarcoma, MN remains a nonspecific disease marker, and other confounding factors may influence it, such as age, gender, diet, lifestyle factors, disease and genetic factors 9) . For example, our study did not have quantitative data about smoking habits, and in the absence of such data, the simple comparison of smokers versus nonsmokers might be misleading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MN can be formed from acentric chromosomal fragments or whole chromosomes fail to be segregated to the daughter nuclei during mitotic cellular division (Fenech and Bonassi 2011). Thus, these genotoxicity tests are well-established markers for the determination of the genotoxic effects of compounds.…”
mentioning
confidence: 99%